EFFECT OF MAGNETIC FIELD FROM MOBILE PHONE ON CENTRAL NERVOUS SYSTEM (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Devices such as mobile phones, wireless internet modems, and radios and televisions, which occupy an important place in social life, produce electromagnetic fields (EMFs). Widespread use of these devices in daily life increases the intensity of exposure to EMFs on a day to day basis. Investigation of the effects on health of devices such as mobile phones used in close proximity to the body is attracting considerable interest from scientists. Mobile phones manufactured using the latest technology operate in a high frequency range (3003000 MHz). This further heightens concerns regarding the effect of mobile phones on human health. Most Global System for Mobile Communications (GSM) operators in Europe, Asia, and Africa use a frequency of 900 MHz. With the rapid development of electronic information and communication techniques, exposure to electromagnetic fields (EMFs) has increased dramatically. Some studies have focused on the biological effects of electromagnetic radiation. Microwave radiation has been reported as producing adverse effects in the central nervous system (CNS), including headache, sleep disorders, anxiety, cognitive dysfunction and neurogenesis impairment in both humans and animals. However, the direct effects of microwave radiation on neurodevelopment and the underlying mechanisms for any such effects remain unknown. As per todays global scenario use of mobile phone is increasing day by day for communication. Due to its constant use, the electromagnetic radiation (EMR) emitted from the cell phone, base station and other household appliances cause adverse effects on human health. There is an increase concern about the interaction of EMR generated from mobile phones, with the human organs specially with brain because of its close and long proximity to human brain during the mobile usage. Concerns have shown whether these exposures could have effect on brain and central nervous system (CNS).